(untitled) (Revista Educação, Artes e Inclusão, 2021)
The present research sought to investigate the relations among children from 5 to 12 years old who study in a local public school. In the literature we can see that the creation of these relations can be inhibit or empower the learning process. This is a qualitative research carried out through a sociodramatic methodology. Thirty-six children divided by age in six groups were part of it, It was carried out ten sessions with each group, which were transcribed, and underwent content analysis. The choice of the children was given by the school’s indication. The data analysis shows that children talk about important relations, especially with their family, because they have both relations of acceptance and rejection in the familiar scope. Older children talk more intensely than the younger ones about themes related to their relations at school, which happened to be mostly of rejection. The media becomes an important factor in linking children to the world. With the passing of interventions, we observed the development of relation with nature and with the group of children, being these factors of motivation for the children.